2021
DOI: 10.3389/fimmu.2021.686676
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Induces an Immunological Memory Characterized by Maternal Immune Alterations Through Specific Genes Methylation

Abstract: During pregnancy, the maternal immune system undergoes major adaptive modifications that are necessary for the acceptance and protection of the fetus. It has been postulated that these modifications are temporary and limited to the time of pregnancy. Growing evidence suggests that pregnancy has a long-term impact on maternal health, especially among women with pregnancy complications, such as preeclampsia (PE). In addition, the presence of multiple immunological-associated changes in women that remain long aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Kinder et al showed that a group of fetal‐specific CD8 + T cells functionally exhausted with increased PD‐1 and Lag‐3 expression after pregnancy and maintained protection against fetal loss in subsequent pregnancies 58 . A study by our group also found an increased ratio of PD‐1 + Vδ2 + γδT in women who have experienced PE at least 1 year postpartum 59 . More research is needed to determine whether the PD‐1/PD‐L1 pathway is involved in regulating pregnancy memory.…”
Section: First Generation Of Inhibitory Immune Checkpoint Moleculessupporting
confidence: 51%
See 1 more Smart Citation
“…Kinder et al showed that a group of fetal‐specific CD8 + T cells functionally exhausted with increased PD‐1 and Lag‐3 expression after pregnancy and maintained protection against fetal loss in subsequent pregnancies 58 . A study by our group also found an increased ratio of PD‐1 + Vδ2 + γδT in women who have experienced PE at least 1 year postpartum 59 . More research is needed to determine whether the PD‐1/PD‐L1 pathway is involved in regulating pregnancy memory.…”
Section: First Generation Of Inhibitory Immune Checkpoint Moleculessupporting
confidence: 51%
“…58 A study by our group also found an increased ratio of PD-1 + Vδ2 + γδT in women who have experienced PE at least 1 year postpartum. 59 More research is needed to determine whether the PD-1/PD-L1 pathway is involved in regulating pregnancy memory. immunoglobulin V domain (Table 1).…”
Section: Studiesmentioning
confidence: 99%
“…The placenta, through cytokines and hormones secreted by trophoblast cells, educate uterine maternal immune cells, 31 and determines the immunological environment at the maternal/fetal interface, as well as at the maternal systemic immune system 32–35 . Interestingly, many of the maternal immunological changes that take place during pregnancy remain after the delivery of the fetus, suggesting a long term effect of the pregnancy on the maternal immune system 36 and another major difference from the original conceptualization of pregnancy as a host/graft immunological process.…”
Section: Figurementioning
confidence: 99%
“…Signals form the embryo will inhibit the expression of chemokines and will shift the phenotype of local macrophages leading to tolerance, placentation and fetal growth by trophoblast educate uterine maternal immune cells, 31 and determines the immunological environment at the maternal/fetal interface, as well as at the maternal systemic immune system. [32][33][34][35] Interestingly, many of the maternal immunological changes that take place during pregnancy remain after the delivery of the fetus, suggesting a long term effect of the pregnancy on the maternal immune system 36 and another major difference from the original conceptualization of pregnancy as a host/graft immunological process. The second explanation proposed by Medawar was a generalized maternal immune suppression, similar to what is induced in transplant patients.…”
mentioning
confidence: 99%
“…The placenta is a highly specialized organ that develops during pregnancy to ensure the growth and the normal progress of the pregnancy. This organ also plays an important role in protecting the fetus from environmental harms, including those emanating from the maternal immune system [ 1 ]. Among important cells that form the placenta is the cytotrophoblast, a cell type capable of strong adaptation to its environment, as it expresses both the maternal and paternal antigens.…”
Section: Introductionmentioning
confidence: 99%